Subcritical Water Extraction and Hydrolysis of Cod (Gadus morhua) Frames to Produce Bioactive Protein Extracts - Rodrigo Melgosa; Marta Marques; Alexandre Paiva; Ana Bernardo; Naiara Fernández; Isabel Sá-Nogueira; Pedro Simões (Foods, 2021)
The valorization of Atlantic cod (Gadus morhua) frames from a filleting industry was investigated using subcritical water extraction and hydrolysis (SBW) at different temperatures (90, 140, 190 and 250 °C) and 100 bar to obtain extracts rich in proteins, peptides and amino acids. Up to 57.7 g of extract per 100 g of codfish frames were obtained, with nearly total recovery of the protein fraction. At each temperature, protein extracts of decreasing molecular weight were obtained, according to SEC-GPC results. Most of the protein present in the raw material and extracts was collagen and collagen fragments, as suggested by the amino acid profile. Codfish SBW extracts did not show cytotoxicity in the range of concentrations tested and the protein extract obtained at the lowest temperature (90 °C) showed the highest anti-inflammatory potential in human intestinal epithelium cell model. The mineralized residue left after SBW treatment of cod frames was identified as practically pure, crystalline, hydroxyapatite, that may find applications in biomedical field and hard-tissue engineering. This study shows the possible valorization of cod frames using green extraction methods such as SBW process to obtain protein extracts for food and nutraceutical applications.